Therapeutic efficacy of the Ginkgo special extract EGb761® within the framework of the mitochondrial cascade hypothesis of Alzheimer's disease. (16th March 2019) - Müller, Walter E.; Eckert, Anne; Eckert, Gunter P.; Fink, Heidrun; Friedland, Kristina; Gauthier, Serge; Hoerr, Robert; Ihl, Ralf; Kasper, Siegfried; Möller, Hans-Jürgen
Abstract: Objectives: The mitochondrial cascade hypothesis of dementia assumes mitochondrial dysfunction as an important common pathomechanism for the whole spectrum of age-associated memory disorders from cognitive symptoms in the elderly over mild cognitive impairment to Alzheimer's dementia. Thus, a drug such as the Ginkgo special extract EGb 761 ® which improves mitochondrial function should be able to ameliorate cognitive deficits over the whole aging spectrum. Methods: We review the most relevant publications about effects of EGb 761 ® on cognition and synaptic deficits in preclinical studies as well as on cognitive deficits in man from aging to dementia. Results: EGb 761 ® improves mitochondrial dysfunction and cognitive impairment over the whole spectrum of age-associated cognitive disorders in relevant animal models and in vitro experiments, and also shows clinical efficacy in improving cognition over the whole range from aging to Alzheimer's or even vascular dementia. Conclusions: EGb 761 ® shows clinical efficacy in the treatment of cognitive deficits over the whole spectrum of age-associated memory disorders. Thus, EGb 761 ® can serve as an important pharmacological argument for the mitochondrial cascade hypothesis of dementia.